Relaxation processes of metallic materials during plastic deformation - Zasimchuk, E. E.; Turchak, T.V.; Baskova, O. I.; Tarasenko, L.V.; Gatsenko, A. S. (Reports of the National Academy of Sciences of Ukraine, 2015)
The structure formation in plastically deformable metal materials during the deformation and fracture is investigated. The results of experimental studies of nickel deformed by rolling to 50–80% with the use of the statistical analysis of TEM structures are presented. It is shown that the deformational softening is caused by the crystallization of a liquid-like structure of the channel hydrodynamic plastic flow of the material. The possible mechanism of recrystallization and the properties of relaxation structures, from micrograins (nuclei of crystallization) to recrystallized grains are considered.